Plastic debris characteristics and the effect of wind on Bawean Island Beaches, East Java, Indonesia - Nurhafizh Sri Albarra; Defri Yona; Muhammad Arif Asadi; Syarifah Hikmah Julinda Sari; Riski Agung Lestariadi; Akhmad Amirudin (Depik, 2024)
Characteristics of plastic debris were assessed among two types of beaches on Bawean Island (windward and leeward) to analyze its sources and long-term effects. Plastic debris was collected inside a 5 x 5 meter transect with five transect plots on each beach per 20 meters. Samplings were carried out three times at intervals of seven days from six different beaches. The average abundances of plastic debris were almost similar between leeward (0.1690.123 pcs m-2) and windward beaches (0.8410.577 pcs m-2). On the other hand, in terms of weight, leeward beaches contained a very low value of debris (0.9270.746 g m-2) compared to windward beaches (4.4793.551 g m-2). Sheets on the windward beaches and wholes on the leeward beaches dominate the shape of plastic debris with the average size was 1520 cm. The color on both type of beaches was dominated by white (38%) and blue (12%). The weathering intensity is 48% on the leeward beach and 52% on the windward beach. The absence of significant differences in size, color, and weathering intensity implies that the debris found came from the same source. The large size and low weathering intensity of the plastic debris means that the debris has not been exposed to hydro-oceanographic factors for an extended period and they came from a local source. The difference in abundance and shape of plastic debris suggests that wind still plays a vital role in shaping the characteristics of plastic debris on Bawean Island.Keywords:Marine DebrisPlastic WeatheringWind DirectionMarine PollutionMacroplastic